ANALISIS FINANCIAL DISTRESS SAAT KRISIS KEUANGAN GLOBAL : STUDI EMPIRIS PADA BUMN NON KEUANGAN - Nakamura, Tiffany Mica (Media Akuntansi dan Perpajakan Indonesia, 2021)
This study aims to determine the differences and levels of accuracy of the Altman Z-Score, Springate S-Score, and Zmijewski X-Score in predicting financial distress before, during, and after the global financial crisis. The sample in this study used nine state-owned companies in the non-financial sector, which were listed on the Indonesia Stock Exchange for the period 2005–2012. Data collection used secondary data from the company’s annual reports—data analysis methods using the Kruskall - Wallis test as a comparative test used to determine differences. This study indicates no differences in predictions before, during, and after the global financial crisis. The accuracy test states that the three prediction models are appropriate, but the Altman Z-Score is the model with the highest accuracy level.